Effects of cigarette smoking and physical activity on severity of primary open angle glaucoma in chinese patients - Othman, Khairuddin (2016)
INTRODUCTION Primary open angle glaucoma (POAG) is the most common type of glaucoma. Progression of glaucoma is common; despite good control of intraocular pressure (IOP). Factors associated with progression of glaucoma can be divided into nonmodifiable and modifiable risk factors. There is limited research on identification of modifiable risk factors. Modifiable risk factor include cigarette smoking and physical activity. There are evidences on the potential association between current cigarette smoking and physical activities on the development of POAG. However, there is no available evidence on the potential association between cigarette smoking and physical activities and severity of POAG. OBJECTIVE To determine the association between cigarette smoking and physical activity on the severity of primary open angle glaucoma (POAG) in Malaysian Chinese patients. METHODOLOGY A cross-sectional study was conducted between November 2014 and March 2016 in eye clinic of Hospital Kuala Lumpur and Hospital Universiti Sains Malaysia. Only patients who were able to provide two consecutive reliable and reproducible Humphrey visual field 24-2 analyses were included. Severity of glaucoma was based on modified AGIS scoring system on HVF and divided into mild, moderate and severe glaucoma. Face to face interview was conducted to assess their smoking habits and physical activities. Their smoking status was obtained using validated questionnaire from Singapore Malay Eye Study (SiMES). Cigarette smoking was divided into active smoker, ex-smoker, passive smoker and non-smoker. Duration of smoking and number cigarette per day was also documented. Physical activity status was assessed based on validated Bahasa Malaysia version of International Physical Activity Questionnaire (IPAQ). Based on their physical acticities over 7 days, POAG patients were divided into mild, moderate and heavy physical activity. The duration of physical activity and measurement of energy requirement (METs) was also calculated. Univariate analysis was conducted to examine other risk factors for severity of glaucoma and AGIS score. The association of smoking and physical activity with AGIS score was analysed using multiple linear regression (MLR). RESULTS A total of 150 Chinese patients were recruited (103 male and 47 female). There was significant association between cigarette smoking and severity of glaucoma (p <0.001). Smoking increases the AGIS score by 3.3 (adjusted b 3.26, 95% CI 1.67, 4.86, p <0.001). However, there was no significant association in duration of smoking (in years) and duration since stopped smoking (in years) with severity of glaucoma. There was significant inverse relationship between physical activity and AGIS score. Every increase in physical activity reduces the AGIS score by 4.39 (adjusted b -4.39,